PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN PEMEBILIAN PRODUK UNILEVER INDONESIA CABANG MAKASSAR - Muslim; Muh. Salim Sultan; Abdul Khalik (Jurnal Bisnis dan Kewirausahaan, 2023)
This study aims to determine and determine the partial influence as well as the simultaneous influence of the Promotion Mix which includes advertising, Personal Selling, Promotion Selling and Public Relation on Product Purchasing Decisions of Unilever Indonesia Makassar Branch. To analyze and find out the variables that have a dominant influence on Product Purchasing Decisions of Unilever Indonesia Makassar Branch. The data collection technique uses a questionnaire and documentation as a means to obtain accurate data, then the data is processed using the SPS Version 20 Program. Data analysis methods use the Multiple Linear Regression Analysis Tool. The measurement scale in the study uses the Likert Scale. The results showed that Advertising Partially had a positive and not significant effect on purchasing decisions for Unilever Indonesia Makassar Branch products. Personal Selling, Promotion Selling and Public Relations have a positive and significant effect on purchasing decisions for Unilever Indonesia Makassar Branch products. Meanwhile, simultaneously Advertising, Personal Selling, Promotion Selling and Public Relations have a positive and significant effect on purchasing decisions for Unilever Indonesia Makassar Branch products. The variable that has a dominant effect is the Public Relations variable with a beta value of 0.477 and a significance level of 0.000 <0.005.